Pengaruh Struktur Modal, Ukuran Perusahaan Dan Umur Perusahaan Terhadap Nilai Perusahaan: Survey Pada Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Dini Anggraini; R.M. Rum Hendarmin; Aris Munandar (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to determine the effect of capital structure, firm size and firm age on firm value in food and beverage companies listed on the Indonesia Stock Exchange. This type of research is quantitative research. The sample used was 19 companies from a population of 26 food and beverage companies listed on the Indonesian stock exchange in 2015-2019. This study uses secondary data, the data analysis method used is the panel data regression analysis method. The results showed that simultaneously capital structure, firm size and firm age had an effect on firm value. Then, partially capital structure and firm age have a significant negative effect on firm value. On the other hand, firm size has no significant negative effect on firm value. The amount of the Adjusted R Square (R2) is 0.692658 or 69.26%, which means that the ability of the independent variable to explain the variation in the dependent variable change is 69.26%, while the rest is 0.30% (100% - 69.26%) is influenced by other factors outside the research variables. The results of this study are expected to be taken into consideration by companies when they want to increase company value.